A quality control study on the feminine care product line of Kimberly-Clark Philippines, Inc. - Basilla, Mary Ann; Galang, Celiamor; Panugaling, Dianne Karryle (Quezon City College of Engineering, University of the Philippines Diliman, 2006)
Kimberly-Clark Philippines, Inc is one of the nation's top manufacturers of health and hygiene products. But being an established company doesn't mean that they will not have problems in quality. In fact, they should give more importance on maintaining their high quality standards to be able to stay in the race for market share. This study focuses on the feminine care product line, Brand X and Brand Y, called as such, due to confidentiality purposes. The group was asked by the company to verify the sampling plan that they recently employed. Several on-line operators were complaining regarding it. The company wanted a study that will prove that the current sampling quantity was enough. Given this problem, the group gathered all pertinent data through series of plant visits, interviews and process observation. All the data regarding the current sampling plan was provided by the company through Exponential Weight and Moving Average (EWMA), a criterion used by Kimberly-Clark Corporation. The group's plan of solution was to construct an Operating Characteristics curve that relates the ß-risk (probability of detecting a shift on the first subsequent sample) and k (desired magnitude of the shift to be detected). From these, the number of samples that will be used will be determined. Sampling frequency will be upon the company's discretion, taking into account the group's recommendation and the costs that will be incurred.
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial quality control.
Keywords: Kimberly-Clark Corporation; Feminine hygiene products; Quality control